Estudo multicêntrico brasileiro de 71 pacientes com arterite de Takayasu juvenil: características clínicas e angiográficas - Clemente, Gleice [UNIFES] (2016)
Objective: To describe the clinical and angiographic characteristics of Takayasu's arteritis in Brazilian children and adolescents. Methods: A retrospective data collection was performed in 71 children and adolescents followed in 10 Brazilian reference centers in Pediatric Rheumatology. The evaluation was carried out in three different time points: from onset of symptoms to diagnosis, from the 6th to 12th month of diagnosis, and in the last visit. Results: Of 71 selected patients, 51 (71.8%) were girls. The mean age of onset of symptoms and of time to diagnosis was 9.2 (+/- 4.2) years and 1.2 (+/- 1.4) years, respectively. At the end of the study, 20 patients were in a state of disease activity, 39 in remission and 5 had evolved to death. The most common symptoms in baseline assessment, second evaluation, and final evaluation were, respectively: constitutional, musculoskeletal, and neurological symptoms. A decrease in peripheral pulses was the most frequent cardiovascular signal, and an increase in erythrocyte sedimentation rate was the most frequent laboratory finding in all three evaluation periods. The tuberculin test was positive in 41% of those tested. Stenosis was the most frequent angiographic lesion, abdominal artery was the most affected segment, and angiographic type IV the most frequent. Most (90%) participants were treated with glucocorticoids, 85.9% required another immunosuppressive drug, and 29.6% underwent angioplasty. Conclusion: This is the largest study on juvenile-onset Takayasu arteritis, and a high number of patients under the age of 10 years, with predominance of constitutional symptoms early in the disease, was observed. (C) 2016 Elsevier Editora Ltda. All rights reserved.